2007
DOI: 10.1111/j.1365-2036.2007.03498.x
|View full text |Cite
|
Sign up to set email alerts
|

Alpha fetoprotein, ultrasound, computerized tomography and magnetic resonance imaging for detection of hepatocellular carcinoma in patients with advanced cirrhosis

Abstract: SUMMARY BackgroundSerum alpha fetoprotein (AFP), ultrasound, computerized tomography scanning, and magnetic resonance imaging are commonly used to screen for hepatocellular carcinoma (HCC) in patients with cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 21 publications
(35 reference statements)
1
55
0
3
Order By: Relevance
“…16 Previous studies have demonstrated that the baseline AFP level is a significant prognostic factor for various stages of HCC. [16][17][18][19][20][21][22] Recently, Chan and colleagues reported that a decline in the post-treatment AFP level was associated with radiologic tumor response and survival in patients with advanced HCC who received doxorubicin-based combination chemotherapy. 23 Vora et al also reported that post-treatment AFP changes were closely associated with clinical outcomes in patients who received various types of systemic therapy.…”
mentioning
confidence: 99%
“…16 Previous studies have demonstrated that the baseline AFP level is a significant prognostic factor for various stages of HCC. [16][17][18][19][20][21][22] Recently, Chan and colleagues reported that a decline in the post-treatment AFP level was associated with radiologic tumor response and survival in patients with advanced HCC who received doxorubicin-based combination chemotherapy. 23 Vora et al also reported that post-treatment AFP changes were closely associated with clinical outcomes in patients who received various types of systemic therapy.…”
mentioning
confidence: 99%
“…In order to improve the specificity of AFP in the diagnosis of HCC, AFP-L3 has been developed. AFP-L3 levels had sensitivities and specificities that ranged from 36-96% and 89-94%, respectively, though for the diagnosis of small HCCs, the specificity is relatively low, around 20% (20,28). Pre-treatment AFP-L3 values have also been reported to be correlated with poorly differentiated cancer and poor prognosis (40,41).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, AFP and DCP have nearly equal sensitivity, although DCP has higher specificity (23)(24)(25)(26). We set the cut-off level of AFP-L3 and DCP as 10% and 40 mAU/ml, respectively, based on previous reports (20,(23)(24)(25)(26)28,40,41).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations